2021
DOI: 10.3389/fcell.2021.739321
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of H3K27me3 in Porcine Embryonic Muscle Development

Abstract: The trimethylation of histone H3 lysine 27 (H3K27me3) is one of the most important chromatin modifications, which is generally presented as a repressive mark in various biological processes. However, the dynamic and global-scale distribution of H3K27me3 during porcine embryonic muscle development remains unclear. Here, our study provided a comprehensive genome-wide view of H3K27me3 and analyzed the matching transcriptome in the skeletal muscles on days 33, 65, and 90 post-coitus from Duroc fetuses. Transcripto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Previous studies also demonstrated that myogenic transcription factors were repressed by H3K27me3 during cell proliferation in PSCs, while H3K27me3 depletion promoted myogenic differentiation [55] . Our previous sequencing results [36] revealed that RASGRP1 has a significant H3K27me3 enrichment peak in its promoter. Thus, we aimed to investigate the function of RASGRP1 in myogenesis and explore the regulatory function of H3K27me3 in RASGRP1 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies also demonstrated that myogenic transcription factors were repressed by H3K27me3 during cell proliferation in PSCs, while H3K27me3 depletion promoted myogenic differentiation [55] . Our previous sequencing results [36] revealed that RASGRP1 has a significant H3K27me3 enrichment peak in its promoter. Thus, we aimed to investigate the function of RASGRP1 in myogenesis and explore the regulatory function of H3K27me3 in RASGRP1 .…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that dysregulation of RASGRP1 leads to the occurrence of cancers [ 23 28 ] and other diseases [ 29 33 ] related to the body’s immunity [ 34 , 35 ]. Our previous study found that RASGRP1 may regulate pig embryonic myogenesis, which was regulated by H3K27me3 through chromatin immunoprecipitation-sequencing (ChIP-seq) and RNA-sequencing of the longissimus dorsi muscle in Duroc pig embryos at gestation days 33 (E33), 65 (E65), and 90 (E90) [36] . However, the detailed function of this gene in regulating myogenesis is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that changes in DNA methylation are one of several epigenetic mechanisms that influence gene regulation, which also include histone modification, long non-coding RNAs, and chromatin accessibility (Ibeagha-Awemu and Zhao 2015). Notably, genomewide H3K27me3 levels have been shown to gradually increase with increasing age in porcine prenatal skeletal muscle (Tan et al 2021), suggesting that other processes may function synergistically with DNA methylation to control muscle-specific gene expression. Characterization of such mechanisms and their dynamics throughout skeletal muscle development will provide a more holistic assessment of chromatin modifications that drive this complex process.…”
Section: Differential Methylation Is Strongly Associated With Differe...mentioning
confidence: 99%
“…To meet this need, recent breakthroughs in multi-omics technology have been extensively exploited in pig samples. Studies have examined the dynamic alterations in DNA methylation patterns [16,17], fluctuations in mRNA or noncoding RNA expression profiles [18][19][20], dynamic changes in chromatin accessibility [21,22], alterations in the three-dimensional structure of the genome [23], and changes in the histone modifications associated with diverse cis-regulatory elements [24]. Undoubtedly, they have markedly advanced our comprehension of the genetic regulatory mechanisms governing the development of pig skeletal muscles.…”
Section: Introductionmentioning
confidence: 99%